2015
DOI: 10.5194/acp-15-12935-2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical components of aerosol particles in different haze regions in China from 2006 to 2013 and contribution of meteorological factors

Abstract: Abstract. Since there have been individual reports of persistent haze-fog events in January 2013 in central-eastern China, questions on factors causing the drastic differences in changes in 2013 from changes in adjacent years have been raised. Changes in major chemical components of aerosol particles over the years also remain unclear. The extent of meteorological factors contributing to such changes is yet to be determined. The study intends to present the changes in daily based major water-soluble constituen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 37 publications
0
55
0
Order By: Relevance
“…Particularly, in the last 8 years between 2010 and 2017, the mean of PLAM increased more than the growth rate of the mean of each of the previous 10 years, which exhibited more noticeable unfavorable weather conditions. When the PM 2.5 mass pollution accu-mulated to a certain extent, it caused the further deterioration of weather conditions, which has been found in almost all HPEs in the Beijing area since 2013 (Zhong et al, 2017(Zhong et al, , 2018Zhang et al, 2017). Therefore, we hypothesized that the substantial rise in mean PLAM between 2010 and 2017 should have benefited from the further worsening of meteorological conditions caused by higher PM 2.5 mass concentra-tions that reached a certain extent.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Particularly, in the last 8 years between 2010 and 2017, the mean of PLAM increased more than the growth rate of the mean of each of the previous 10 years, which exhibited more noticeable unfavorable weather conditions. When the PM 2.5 mass pollution accu-mulated to a certain extent, it caused the further deterioration of weather conditions, which has been found in almost all HPEs in the Beijing area since 2013 (Zhong et al, 2017(Zhong et al, , 2018Zhang et al, 2017). Therefore, we hypothesized that the substantial rise in mean PLAM between 2010 and 2017 should have benefited from the further worsening of meteorological conditions caused by higher PM 2.5 mass concentra-tions that reached a certain extent.…”
Section: Resultsmentioning
confidence: 96%
“…(2) for the PLAM Zhang et al, 2009). This index has been employed to evaluate the contribution of meteorological factors to changes in atmospheric composition and optical properties over Beijing during the 2008 Olympic Games, identify the contribution of specific meteorological factors to a 10-day haze-fog event in 2013 , estimate the relative contribution of meteorological factors to changes in aerosol mass concentrations and chemical compositions in different regions of China during winter from 2006 to 2013 and distinguish the feedback effect of meteorological conditions on the explosive increase in PM 2.5 mass concentration during accumulation stages in the Beijing area (Zhong et al, 2017;Zhang et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…3.3, we also found that the effects of approximated changes in temperature between 1960 and 2010 on PM 2.5 concentration are dominant by changes in PBLH and wind fields. Previous studies have pointed out the occurrences of haze events are highly associated with atmospheric circulation anomalies (Chen and Wang, 2015;Zhang et al, 2016). Thus, changes in atmospheric circulations may be another important cause of growing haze pollution in addition to emission changes.…”
Section: Implications For the Effects Of Emission And Meteorology Chamentioning
confidence: 99%
“…The hygroscopicity of atmospheric particles can determine how particles change with varying relative humidity (RH). Thus, RH has a key impact on the physical properties of particles, including size, morphology, and wavelength‐dependent refractive indices (Freney et al, ; L. Zhang et al, ; Wise et al, ). In addition, water uptake of atmospheric aerosols influences their atmospheric lifetimes, reactivity, effects on air quality, and, ultimately, their effects on human health (Ervens, ; Hodas, Sullivan, et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%